"He's on his dying bed": Next-of-kin's experiences of the dying body. Issue 1 (2nd January 2016) - Drentea, Patricia; Williams, Beverly R.; Bailey, F. Amos; Burgio, Kathryn L.
ABSTRACT: For family members of dying patients who have grown accustomed to providing daily body care, the transition from home to hospital is stressful. The authors used the experiences surrounding death for 78 U.S. veterans who died in a Veterans Affairs hospital. The research is based on interviews conducted with the decedent's next-of-kin. Secondary qualitative analysis of previously-coded transcribed interviews was used. Themes of social disorganization and a loss of control over the body emerged. Next-of-kin experienced the physical and functional breakdown of their loved one's body. Understanding the nature of the loss of control may help alleviate the loss of control may help alleviate the strain on families.